Porous silica matrix obtained from pyrex class by hydrothermal treatment: Characterization and nature of the porosity - Sigoli, Fernando Aparecido [UNESP]; Feliciano, Sérgio [UNESP]; Giotto, Marcus Vinicius; Davolos, Marian Rosaly [UNESP]; Jafelicci Júnior, Miguel [UNESP] (Amer Ceramic Soc, 2003)
A novel porous silica matrix has been prepared from Pyrex glass, using hydrothermal treatment under saturated-steam condition. This process makes it possible to obtain, in one step, a silica support formed of a homogeneously distributed and interconnected macropore microstructure. The new matrix contains silanol groups that can be used in reactions of surface modification to provide a hybrid material and a selective macrofiltration membrane, and also it can improve chemical inertness. The porous matrix is noncrystalline as obtained and, after thermal treatment at temperatures higher than 950degreesC, exhibits an X-ray pattern characteristic of alpha-cristobalite and low volume contraction. The present samples were characterized by scanning electron microscopy, mercury intrusion porosimetry, nitrogen adsorption-desorption isotherms, infrared spectroscopy, X-ray powder diffractometry, atomic absorption, and high-resolution solid-state nuclear magnetic resonance. The results present a new way of producing a macroporous silica matrix.
Keywords: Adsorption isotherms; Desorption; Glass; Heat treatment; Hydrothermal synthesis; Infrared spectroscopy; Microstructure; Nuclear magnetic resonance; Porosity; Porous materials; Scanning electron microscopy; Steam; Surface treatment; X ray powder diffraction; Mercury intrusion porosimetry; Silica